Improvement Model Damping Low Frequency Oscillations Presence UPFC by Cuckoo Optimization Algorithm - M. Yousefi Anarkooli; H. Afrakhteh (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Low frequency oscillation (LFO) is a negative phenomenon repeated for the power system increases the risk of instability. In recent years, power systems stabilizer (PSS) for damping low frequency oscillations is used. With FACTS devices such as integrated power flow controller (UPFC) can control power flow and  transient   stability increase.  So, UPFC low   frequency oscillation damping can be used instead of PSS. UPFC through direct control voltage and low frequency oscillation damping can be improved. In this study, a single linear model of synchronous machine connected to an infinite bus Heffron-Philips in the presence of UPFC to improve low frequency oscillation damping is used. The selection of the output feedback parameters for the UPFC controllers is converted to an optimization problem which is solved by cuckoo optimization algorithm (COA). COA, as a new evolutionary optimization algorithm, is used in multiple applications. This optimization algorithm has a strong ability to find the most optimistic results for dynamic stability improvement. The controller UPFC and damping in MATLAB software environment is designed and simulated. The simulation was performed for a variety of loads and for various loads and more effective UPFC controller electromechanical oscillation damping compared to other algorithm types is shown.